ECONOMIC SIGNIFICANCE OF FINANCING RELATIONS IN THE AGRICULTURAL SECTOR - Ishniyazov Bakhrom Normamatovich (American Journals, 2024)
In this article, it is important to form financial and credit relations in the industry and provide the industry with preferential loans and funds, improve the financial situation, increase profitability, and provide loans and financial support from the state to enterprises operating at a loss. And this will have a positive effect on the increase of financial stability and solvency of enterprises in the future, and a sharp reduction of debtor and creditor debts.
Keywords: Source of financing, financial system, credit system, biological processes, industrial characteristics, production cycle, fluctuations, costs, volume of income, authorized capital, elasticity of demand, physiological needs, depreciation payments.